A Synodal Approach to Reveal the Presence of Christ in the World!: An anglican perspective on inculturation - Ernest, Ian (Lateranum, 2022)
The presentation of this paper, "An Anglican perspective on Inculturation" comes at an opportune time. The Synodal process initiated by His Holiness Pope Francis calls for an openness of spirit that favours mutual listening. Therefore, this paper comes as a form of a contribution in our ecumenical conversations as it aims at engaging Christians from different orientations to learn from each other. The different aspects on how the Anglican Communion presents the Incarnate Christ in the diversity of the world we live in, are informative and thought provoking as they provide an historical and missional perpsectives to our life as a Church for today and the future.